STRUCTURAL EQUATION MODELS: MATHEMATICAL REASONING ABILITIES AND GEOMETRIC PROBLEM-SOLVING ABILITIES - Anggoro, Abdurrobbil Falaq Dwi; Wardono, Wardono; Mariani, Scolastika; Susilo, Bambang Eko; Hidayat, Riyan; Tommy Tanu Wijaya (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to test the compatibility of structural equation (SEM) models to determine the relationship between mathematical reasoning ability and geometry problem solving ability. Using an ex-post facto research design, this study took a random sample of 100 students from a total of 296 mathematics education student population at a university in Lubuklinggau. Data were collected through mathematical reasoning tests and geometry problem-solving tests, then analyzed using the Lisrel 8.8 and SPSS programs. The results of the analysis show a very significant path coefficient, which proves that mathematical reasoning ability has a positive direct relationship with geometry problem-solving ability. This means that an increase in reasoning skills will be followed by an increase in the ability to solve geometry problems. In conclusion, this study confirms the existence of a direct relationship between the two variables, where mathematical reasoning ability contributes 15.13% to the improvement of geometry problem-solving ability. Keywords: Ability, Mathematical reasoning, Geometric Problem Solving, SEM, Lisrel